Animal Model of Pancytopenia and Bone Marrow Function Diagnosis of Domestic Rabbits - Mohammed E. Mansur (Journal of Global Pharma Technology, 2016)
The present research aims at showing the effects of extracts of some plants seeds (Nigella sativa, Medicago sativa, Eruca sativa, Ocimum basilicum, Vitis vinifera, Portulaca oleracea) in animals that are induced by a type of drug Azathioprine as animal model of pancytopenia. Several reports have shown that plant extracts are used as an alternative to chemotherapy in many cases of diseases. The research was conducted on forty white rabbit (five weeks old), after weaning, weighing between 500-700 grams, the method of work included eight groups, the numbers of blood cell types that indicate the effectiveness of bone marrow were measured ( RBC, WBC, Thrombocytes, IRF, IPF,IGs, Schistocytes, reticulocyte and ANC),the extracts showed different effects in terms of their ability to improve or re-develop bone marrow to produce blood cells, Ocimum basilicum extract showed a higher effect than the rest of the extracts in pancytopenia treatment, which gave a clear effect on improving bone marrow efficiency.